2016
DOI: 10.1021/jacs.6b02404
|View full text |Cite
|
Sign up to set email alerts
|

Peroxo and Superoxo Moieties Bound to Copper Ion: Electron-Transfer Equilibrium with a Small Reorganization Energy

Abstract: Oxygenation of [Cu2(UN-O−)(DMF)]2+ (1), a structurally characterized dicopper Robin–Day class I mixed-valent Cu(II)Cu(I) complex, with UN-O− as a binucleating ligand and where dimethylformamide (DMF) binds to the Cu(II) ion, leads to a superoxo-dicopper(II) species [CuII2(UN-O−)(O2•−)]2+ (2). The formation kinetics provide that kon = 9 × 10−2 M−1 s−1 (−80 °C), ΔH‡ = 31.1 kJ mol−1 and ΔS‡ = −99.4 J K−1 mol−1 (from −60 to −90 °C data). Complex 2 can be reversibly reduced to the peroxide species [CuII2(UN-O−)(O22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
85
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 59 publications
(99 citation statements)
references
References 78 publications
14
85
0
Order By: Relevance
“…Recent works have shown the possibility to indirectly estimate the redox potential of copper–oxygen species by using chemical oxidants . Though attractive, this method requires the use of a large series of chemical reagents, and leads to an approximate value of the standard potential.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent works have shown the possibility to indirectly estimate the redox potential of copper–oxygen species by using chemical oxidants . Though attractive, this method requires the use of a large series of chemical reagents, and leads to an approximate value of the standard potential.…”
Section: Methodsmentioning
confidence: 99%
“…For that purpose, we have developed new cryo‐electrochemical and UV/Vis‐NIR cryo‐spectroelectrochemical setups. Here, we have focused on the unsymmetrical [Cu 2 (UN‐O − )] 2+/+ complexes 1 2+ and 1 + , which react with dioxygen and lead to the discrete superoxo and peroxo species 2 2+ and 3 + , respectively (Scheme ) . These are only stable at low temperatures ( T <200 K) and the direct determination of their thermodynamic and kinetic redox properties, coupled to their authentic UV/Vis‐NIR spectroscopic features, requires a novel cryo‐spectroelectrochemical approach.…”
Section: Methodsmentioning
confidence: 99%
“…In 1996 and 1997, the groups of Tolman and Stack published on the spectroscopic and structural features of dicopper(III) bis- μ -oxide complexes, where dioxygen has been fully reduced by four electrons and the O-O bond has been cleaved [2023]. Peroxodicopper(II) complexes supported by phenolate-bridging ligands have also been described [2427]. Recently, Meyer and coworkers published the crystal structure of a peroxodicopper(II) complex ligated by a pyrazolate-based binucleating ligand [28].…”
Section: Structurally Characterized Copper-dioxygen Speciesmentioning
confidence: 99%
“…Reactive oxygen species are often generated by molecular oxygen binding to redox active metals such as copper and iron in the human body as side product for energy production. Formation and reactivity of reactive oxygen species are well characterized in ligand copper oxygen model chemistry, for example [29][30][31] . Inoguchi and coworkers [32] reported that high glucose level significantly increases reactive oxygen species production in cultured smooth muscle cells (SMCs) and endothelial cells (ECs) detected by electron spin resonance spectroscopy.…”
Section: The Role Of Cannabinoid and Cannabidiol As Antioxidantmentioning
confidence: 99%